ECTOPIC PREGNANCY MANAGEMENT IN AYUB TEACHING HOSPITAL ABBOTTABAD: A TEN YEAR SURVEY - Deeba, Farhat; Khan, Bushra; Khattak, Samina Naseem (Journal of Ayub Medical College Abbottabad, 2012)
Background: Ectopic pregnancy is a common life-threatening emergency in the developing world. It is a cause of maternal morbidity and mortality in the first trimester and these mortalities can be reduced if it is properly managed. The objective of this study was to assess the variable clinical presentations and outcome of treatment of ectopic pregnancy in Ayub Teaching Hospital Abbottabad. Methods: Two hundred and fifty-five patients with ectopic pregnancy managed in Ayub Teaching Hospital over period of 10 years, were included in the study. The clinical presentation, diagnostic modalities and out come of treatment were recorded and analysed. Results: Out of 255 patients 43 (16.86%) had un-ruptured tubal pregnancy, 183 (71.76%) had ruptured ectopic pregnancy and 22 (8.62%) had chronic ectopic pregnancy. At laparotomy, salpingectomy was done in 229 (89.80%) patients, salpingo-ophrectomy in 2 patients (0.78%), linear salpingostomy in 15 (5.88%) patients. Medical treatment was given to 5 patients and 8 patients were treated conservatively. There was no maternal mortality. Conclusion: In spite of various recent advances in the management of ectopic pregnancy, conventional surgical treatment by laparotomy is still the most widely used modality of treatment in our institution. With appropriate and prompt management, maternal mortality due to ectopic pregnancy can be prevented. Keywords: Ectopic pregnancy, conventional surgical management, laparotomy, salpingectomy